Poética del desahogo (2019)
Poética del desahogo is a sustainable fashion project, was inspired by a Colombian army parachute at the end of its useful life. The creative process was materialized by a holistic research approach. Understanding its material properties, to acknowledge the lives that it had touched, as those coming from Colombia's armed conflict. Despite hostile disagreements and opposing views people from different sides of the conflict were invited to a co-creation session. This allowed to develop a human concept, materialized by using sustainable fashion tools as up-cycling and circularity for the creation of the final piece